2015
DOI: 10.2463/mrms.2015-0003
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma of the Head and Neck: Comparison of Diffusion-weighted MRI at b-values of 1,000 and 2,000 s/mm<sup>2</sup> to Predict Response to Induction Chemotherapy

Abstract: Purpose: Recent publications have reported contradictory results of pretreatment diffusion-weighted magnetic resonance imaging (DWI) for the prediction of chemoradiotherapeutic response in primary squamous cell carcinomas of the head and neck (HNSCC). Therefore, we evaluated the diagnostic performance of DWI obtained with both standard (b = 0 and 1,000 s/mm 2 ) and high (b = 0 and 2,000 s/mm 2 ) b-values for predicting response to induction chemotherapy in HNSCCs.Methods: For 25 patients with primary HNSCC who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
(58 reference statements)
3
15
0
1
Order By: Relevance
“…The results showed that the ADC values were higher than the D values, which may be related to the mix-up of perfusion factors in the biexponential model. This finding is consistent with those of other studies on the head and neck [8,38]. IVIM was used to identify the effects of diffusion and perfusion (pseudo-diffusion).…”
Section: Discussionsupporting
confidence: 89%
“…The results showed that the ADC values were higher than the D values, which may be related to the mix-up of perfusion factors in the biexponential model. This finding is consistent with those of other studies on the head and neck [8,38]. IVIM was used to identify the effects of diffusion and perfusion (pseudo-diffusion).…”
Section: Discussionsupporting
confidence: 89%
“…Several authors have also investigated the advantages of using high b values (e.g. b2000) in the assessment of post-treatment head and neck lesions [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…В последнее время в диагностике опухолей головы и шеи применяют ДВ МРТ с более высокими диапазонами значений b-фактора, до b = 1500/2000 [10]. Это объясняется тем, что подобные высокие значения b-фактора способны оценить медленную внутриклеточную диффузию молекул воды, связанную со сложными структурами и клеточными оболочками [12][13][14][15][16]. Большинство видов рака демонстрирует большее ограничение диффузии молекул воды, чем здоровые ткани и доброкачественные процессы, что в свою очередь приводит к более высокой визуальной интенсивности сигнала на томограммах с высоким b-фактором (~b = 800/1000) и более низкой интенсивности сигнала на ИКД-картах, измеряемых в мм 2 /сек (рис.…”
Section: диффузионно-взвешенная мрт (дв мрт Diffusion-weighted Imagiunclassified